A novel polyamide-type cyclophosphazene functionalized rGO/WS2 nanosheets for bismaleimide resin with enhanced mechanical and tribological properties. (June 2019) - Chen, Zhengyan; Yan, Hongxia; Guo, Liulong; Li, Lin; Yang, Pengfei; Liu, Biao
Graphical abstract: Highlights: Cyclophosphazene functionalized rGO/WS2 nanosheets (PHbP@rGO/WS2 ) were successfully prepared by a simple precipitation polymerization approach. BMI composites reinforced with novel PHbP@rGO/WS2 nano-filler had been fabricated. The 0.8 wt% and 0.6 wt% BMI composites exhibited the largest impact and flexural strengths of 21.2 kJ/m 2 and 185.7 MPa, respectively. 0.6 wt% BMI system exhibited the lowest friction coefficient (0.13) and volume wear rate (1.22 × 10 −6 mm 3 /(N·m)). Abstract: Bismaleimide (BMI) composites reinforced with novel polyamide-type cyclophosphazene functionalized rGO/WS2 were successfully fabricated in this paper. RGO/WS2 was firstly functionalized with polyphosphazene (poly (cyclophosphazene-co-branched polyethylenimine)) (PHbP) by a simple precipitation polymerization approach. The microstructure and morphology of as-prepared PHbP@rGO/WS2 were characterized detailedly. The mechanical and tribological properties of virgin BMI and its composites with various amounts of nano-filler (0.2–1.0 wt%) were comparatively investigated. The largest improvements in impact and flexural strengths of BMI composite (21.2 kJ/m 2 and 185.7 MPa, respectively) were observed when the content of PHbP@rGO/WS2 was only 0.8 wt% and 0.6 wt%, increased by 82.8% and 52.0% than those of pure BMI. Furthermore, 0.6 wt% BMI system exhibited the lowest friction coefficient (0.13) and volume wear rate (1.22 × 10 −6 mm 3 /(N·m)), decreased by 69.0% and 92.6% than neat BMI. This is owing to the good dispersibility and self-lubricity of PHbP@rGO/WS2, strong interfacial strength between filler and BMI matrix.